The effect of cognitive and relational social capital on structural social capital and micro-enterprise performance - Rajennd Muniady; Abdullah Al- Mamun; Mohd Rosli Mohamad; P. Yukthamarani Permarupan; Noor Raihani Zainol (2015)
Social capital and its dimensions are highly interrelated, and the outcome of social capital provides entrepreneurs with resources and knowledge that are not available in the first place. The objective of this study is to examine the effect of relational and cognitive social capital on structural social capital and the effect of structural social capital on the performance of micro-enterprises owned and managed by women in Peninsular Malaysia. This study uses a cross-sectional approach, and quantitative data are collected through structured interviews. It was found that cognitive social capital has a significant positive effect on structural social capital, and structural social capital has a significant positive effect on micro-enterprise performance. It was found that relational social capital has a positive but insignificant effect on structural social capital. Therefore, women entrepreneurs should emphasize on making the communication process easier and on ensuring that their business values, norms, interpretation, and meaning are shared and communicated to relevant parties to improve network ties and to build a dense network, which is essential in providing access to resources and knowledge. This, in return, is expected to improve the micro-enterprise performance in Malaysia.